2009
DOI: 10.1292/jvms.001509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Minimum Alveolar Concentration (MAC) of Sevoflurane in Dogs

Abstract: ABSTRACT. It is well known that the minimum alveolar concentration (MAC) of inhalation anesthetic decreases with increasing age. However, there is limited information regarding the effect of age on MAC in dogs. This study was designed to determine the effect of age on sevoflurane MAC in dogs. MAC was determined in 6 young (2 years old) and 6 old beagle dogs (8 to 10 years old) under artificial ventilation. Anesthesia was induced via mask induction and maintained with sevoflurane in oxygen, and MAC was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Differences in study design, individual animal and age may account for variability in MAC results. It is reported that sevoflurane MAC reduced with increasing age of dogs [26], similar to humans [17]. The age of dogs used in the present study were 9 to 11 years, therefore, we surmised that the effect of aging might be a major factor lowering the sevoflurane MAC value.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Differences in study design, individual animal and age may account for variability in MAC results. It is reported that sevoflurane MAC reduced with increasing age of dogs [26], similar to humans [17]. The age of dogs used in the present study were 9 to 11 years, therefore, we surmised that the effect of aging might be a major factor lowering the sevoflurane MAC value.…”
mentioning
confidence: 47%
“…After the dogs were allowed to equilibrate for 60 min at ETSEV 2.8 to 3.0%, the electrical stimulus was applied for 10 sec using an electrical stimulator (SEN3301, Nihon Kohden Co., Tokyo, Japan). Positive response to the electrical stimulus for MAC determination was fixed a purposeful movement defined as substantial movement of the head or extremities and did not include coughing, chewing, swallowing or increasing respiratory effort [26,28]. Positive response for MAC-BAR determination was fixed an increase of either heart rate or mean arterial blood pressure (MABP) over 15% above the value recorded at 1 min before applying the electrical stimulus [15].…”
mentioning
confidence: 99%
“…The six dogs used in the present study were aged 8 to 10 years. It was reported that the sevoflurane MAC was reduced with aging up to approximately 17% in the dogs aged 9 years compared to those in the dogs aged 2 years [30]. Therefore, the age of dogs is considered a primary factor in the lowering of sevoflurane MAC of the control dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of sevoflurane MAC: The sevoflurane MAC was determined by use of the tail clamp method [13,30]. Following the instrumentation, the dogs were treated with or without a single bolus IV of 4 mg/kg tramadol through the 22-gauge catheter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation